Spiritual Intelligence and its Relationship to the Psychological Resilience of Student Mentors in Taif - Al-Aiali, Mashhoor Helal (Journal of Educational and Psychological Sciences, 2022)
The aim of the study was to identify the level of spiritual intelligence and psychological resilience among the student mentors in Taif city, as well as to find out the relationship between spiritual intelligence and psychological resilience, and to reveal the differences in the level of spiritual intelligence and psychological resilience among the members of the study sample according to variables (gender–qualification–experience). To achieve the objective of the study, the researcher relied on the descriptive (relational-comparative) approach to suit the objectives of the study, which aims to identify the facts by collecting, analyzing and interpreting information, and reaching scientific results. The research sample was selected represented by student mentors in Taif, the amount of which was (201) student mentors, and the study tool was the spiritual intelligence questionnaire prepared by & Amram, 2007) (Dryerarabization and codification of Arnout (2007), the psychological resilience prepared by Al-Dosari (2019). The results of the study indicated that the level of spiritual intelligence is very high, and the level of psychological resilience is also high, and a statistically significant correlation was found between spiritual intelligence and psychological resilience in the individuals of the study sample. The study also found that there are no significant differences in spiritual intelligence attributed to (gender-qualification –experience), and also there are no significant differences in psychological resilience between student mentors attributed to (gender-qualification –experience).Based on the findings of the study, the researcher recommends the cooperation of student mentors among themselves in partnership with the guidance and counseling department to implement training programs to develop spiritual intelligence and psychological resilience that qualify them to adapt to the work environment.
Keywords: Spiritual intelligence; psychological resilience; student mento